Fighting misinformation in seismology: Expert opinion on earthquake facts vs. fiction - Dryhurst, Sarah; Mulder, Femke; Dallo, Irina; Kerr, John R.; McBride, Sara K.; Fallou, Laure; Becker, Julia S. (Frontiers in Earth Science, 2022)
Misinformation carries the potential for immense damage to public understanding of science and for evidence-based decision making at an individual and policy level. Our research explores the following questions within seismology: which claims can be considered misinformation, which are supported by a consensus, and which are still under scientific debate? Consensus and debate are important to quantify, because where levels of scientific consensus on an issue are high, communication of this fact may itself serve as a useful tool in combating misinformation. This is a challenge for earth science, where many facts in seismology are still being established. The present study collates a list of common public statements about earthquakes and provides - to the best of our knowledge - the first elicitation of the opinions of 164 earth scientists on the degree of verity of these statements. The results provide important insights for the state of knowledge in the field, helping identify those areas where consensus messaging may aid in the fight against earthquake related misinformation and areas where there is currently lack of consensus. We highlight the necessity of using clear, accessible, jargon-free statements with specified parameters and precise wording when communicating with the public about earthquakes, as well as of transparency about the uncertainties around some issues in seismology.